1999
DOI: 10.1007/s002170050426
|View full text |Cite
|
Sign up to set email alerts
|

Changes of the volatile fraction of cooked chicken meat during chill storing: results obtained by the electronic nose in comparison to GC-MS and GC olfactometry

Abstract: In the present study the changes of the volatile fraction of heat-treated chicken meat in the course of chill storage were observed by using different techniques. It was the aim of the study to compare the results obtained by the new technique of the electronic nose to those gained by GC-MS and GC olfactometry (using comparative aroma extract dilution analysis). Chill storage at 4 7C of cooked chicken meat showed large increases in concentration as well as in flavour dilution factors of typical lipid oxidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 17 publications
2
20
0
Order By: Relevance
“…The consistent pattern of volatile compounds reported herein for poultry meat stored for up to 2 days at 4 °C contrasts with those reported by Siegmund and Pfannhauser12 for cooked chicken stored under the same conditions. These researchers detected differences in volatile fractions after 0, 5, 24 and 48 h of meat storage at 4 °C.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The consistent pattern of volatile compounds reported herein for poultry meat stored for up to 2 days at 4 °C contrasts with those reported by Siegmund and Pfannhauser12 for cooked chicken stored under the same conditions. These researchers detected differences in volatile fractions after 0, 5, 24 and 48 h of meat storage at 4 °C.…”
Section: Discussionsupporting
confidence: 63%
“…Similar to the application of the electronic nose to the determination of the quality of beef, pork and fish, a potential exists for utilising this technology in assessing the microbiological quality of poultry products. Siegmund and Pfannhauser12 used this technology to assess changes in the volatile fraction of cooked chicken meat during chilled (4 °C) storage. These researchers demonstrated that the results obtained with an electronic nose were highly correlated with those obtained using gas chromatography–mass spectrometry (GC–MS) and GC olfactometry.…”
Section: Introductionmentioning
confidence: 99%
“…Electronic nose systems do not give any specific information about the compounds causing the aroma nor about their identity (Siegmund & Pfannhauser, 1999). However, with the aid of appropriate mathematical techniques, like artificial neural networks (ANNs) or statistical methods, the electronic nose could recognize the aroma pattern from a particular sample and help in distinguishing it from other samples (Eklov, Johansson, Winquist, & Lundstrom, 1998;Srivastava, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Siegmund and Pfannhauser [40] used an electronic nose to study the changes of the volatile fraction of heat-treated chicken meat during storage. They compared the results obtained in this study with those obtained with a GC-MS and GC olfactometry.…”
Section: Applications To Meatmentioning
confidence: 99%